Handbook of research on new solutions and technologies in electrical distribution networks - Khan, Baseem, 1987-; Alhelou, Hassan Haes, 1988-; Hayek, Ghassan, 1958- (Advances in computer and electrical engineering (ACEE) book series., 2020)
"This book examines the major issues and technological advancements in the electrical distributor sector"--